A Novel Design of a Miniature Metamaterial Antenna for RFID Reader Applications - A. Ennajih; J. Zbitou; M. Latrach; A. Errkik; L. EL Abdellaoui; A. Tajmouati (Universitas Ahmad Dahlan, 2018)
In this article, we propose a novel design of a dual band antenna based metamaterial for RFID applications. The proposed antenna consists of a rectangular patch using inverted u-slot in radiating element and two split ring resonators loaded in the ground plane. The antenna is printed on an FR4 substrate having athickness of 1.6 mm, permitivitty of 4.4 and loss tanget of 0.025. this antenna is feed by a micostrip line having caracteristique of 50 Ohms. The designed antenna resonates at the UHF band around 900Mz with an input impedance of 87MHz and also, resonates at the ISM band around 2.45GHz with a large bandwidth about 516MHz. The designed antenna is simulated bys using CST and the results is validated by HFSS. After simulation, a prototype of the proposed antenna is fabricated, and the measured results show a good agreement with the simulated one.